Kredyty dla firm: Credit for businesses - Czapski, Grzegorz (Management and Administration Journal, 2021)
This publication analyzes the definitions of the loan and its types that are currently available to businesses. In the introductory part explains the basic concept of the loan, its features and content that should contain the credit agreement. In the following section describes the most frequently granted loans namely: investment, rotary mortgages and overdrafts. In the following section describes the most frequently granted loans namely: investment, rotary mortgages and overdrafts. In the following section describes the most frequently granted loans namely: investment, rotary mortgages and overdrafts.